Theoretical and Methodological Contributions of a Multi-Situated Approach and the Analysis of Migration Routes: The Example of Migration between Morocco and Canada - Stéphanie Garneau (El Colegio de la Frontera Norte, A.C., 2010)
Based on a series of research results on Moroccan migration to Canada, this paper seeks to prove how focusing on the migration routes of a specific national group of migrants and using a multi-situated methodological approach will not lead to the "ethnisizing", culturalizing or nationalizingof the experienced realities, but rather to the placing of actions within their political, cultural, social and economic structuring contexts. By resorting to an inductive approach, this perspective allows us to identify frontiers (in a symbolic sense) other than cultural or national belonging, reminding us of the internal heterogeneity of the studied national group, allowing us to apprehend other decisive factors in the migration route, and favoring our understanding of the plurality of the space practices and integration strategies developed by social actors when facing the concrete opportunities and limitations found during the whole migration process.